Discourses on and Realities of the life of Canines among Arabs and Muslims - Sonbol, Amira (Hawwa, 2014)
This paper is about the power of representation; it takes as specific focus an animal who has been made out to represent all that is impure in Islamic discourses. Not only are dogs regarded as unclean animals, but their entry into a person’s home has been described to be a cause for refusal of angels to enter that home. In other words, good Muslims have to stay away from them. This is odd when the actual history and life of dogs among Arabs is studied, for without dogs Arab merchants trekking over long desert route and peaceful sleeping peasantry all over the Islamic world could not have been protected from attackers, thieves and evil-doers except for vigilant dogs attached to the people involved. Moreover, it is a clear contradiction that the representation of dogs as unclean animals is mostly based on fiqh when in fact the Holy Qur’an has honored the dog in Surat al-Kahf. This paper will discuss these contradictions and discuss the actual place of the dog in Islamic and Arab history and contemporary life to illustrate the contradictions between representation and reality. While this article is not about gender, it is closely related to moral discourses involving women and canines. It is perhaps not coincidental that the last thirty years have seen the anti-dog discourse reach such momentum at the same time as the call for the niqab and the seclusion of women; it is the same voices and groups that seem to espouse both, being conservatively dressed, religiously inclined and observant, and dog-hating seem to go together.